TIPOLOGI PEMIKIRAN KEISLAMAN DI INDONESIA ABAD XXI - Baharuddin Baharuddin (State Islamic University North Sumatra, 2009)
Abstract: The Typology of Islamic Thought in the 21st Century Indonesia. This article outlines the root of Islamic thought in Indonesia and offers a typology of its contemporary developments. Basically it follows the common traditional and modern strands; and although the author adds neo-modernism as a third type he leaves neo-traditionalism untouched. Realising the basic problems of the existing trends, he offers a method of reconciling them.Kata Kunci: Islam tradisional, Islam modernis, Islam neo-modernis